2018
DOI: 10.1111/chd.12683
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance analysis in the management of heart failure in adult patients with congenital heart disease

Abstract: | INTRODUC TI ONFluid retention with dyspnea is the most often encountered cause of rehospitalization after acute heart failure (HF). Decompensated HF generally leads to fluid overload caused by elevated ventricular filling pressure or neurohormonal activation. Thus, the ability to recognize and quantify fluid retention is critical for the treatment of HF; however, optimal markers for the presence of fluid retention have yet to be identified. Brain natriuretic peptide (BNP) testing, chest radiography, cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Lindholm et al [ 22 ] also performed a longitudinal study including over 500,000 participants and determined that leg bioimpedance was inversely correlated with new-onset heart failure and that by combining the leg bioimpedance with clinical parameters such as age, sex, and history of myocardial infarction, accurate prediction of heart failure could be achieved. In another study [ 23 ] on participants with congenital heart disease, bioelectrical impedance correlated with heart failure severity. In contrast to these prior studies, we sought to evaluate the performance of intrathoracic bioimpedance measured using a novel dry electrode for detecting acute decompensated heart failure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lindholm et al [ 22 ] also performed a longitudinal study including over 500,000 participants and determined that leg bioimpedance was inversely correlated with new-onset heart failure and that by combining the leg bioimpedance with clinical parameters such as age, sex, and history of myocardial infarction, accurate prediction of heart failure could be achieved. In another study [ 23 ] on participants with congenital heart disease, bioelectrical impedance correlated with heart failure severity. In contrast to these prior studies, we sought to evaluate the performance of intrathoracic bioimpedance measured using a novel dry electrode for detecting acute decompensated heart failure.…”
Section: Resultsmentioning
confidence: 99%
“…Lindholm et al [ 22 ] determined that leg bioimpedance was inversely correlated with heart failure incidence, and by combining leg bioimpedance with demographic information, they obtained accurate heart failure predictions. Sato et al [ 23 ] evaluated parameters from bioelectrical impedance analysis in participants with congenital heart disease and determined that the edema index obtained from bioelectrical impedance analysis could also be a marker for heart failure severity.…”
Section: Introductionmentioning
confidence: 99%
“…BIA has been applied for the water management of hemodialysis patients and also recently for the water management of heart failure and cardiac surgery patients [16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the EI was a useful marker for heart failure [16][17][18] and the phase angle was a predictive marker for cardiac surgery [12][13][14][15]. The EI shows the ratio between intra-and extracellular water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation